Bromodomains in Human-Immunodeficiency Virus-Associated Neurocognitive Disorders: A Model of Ferroptosis-Induced Neurodegeneration - Sfera, Adonis; Thomas, Karina G.; Andronescu, Christina V.; Jafri, Nyla; Sfera, Dan O.; Sasannia, Sarvin; Zapata-Martín del Campo, Carlos M.; Maldonado, Jose C. (Frontiers in Neuroscience, 2022)
Human immunodeficiency virus (HIV)-associated neurocognitive disorders (HAND) comprise a group of illnesses marked by memory and behavioral dysfunction that can occur in up to 50% of HIV patients despite adequate treatment with combinatory antiretroviral drugs. As iron dyshomeostasis exacerbates HIV-1 infection, and Alzheimer's disease prevalence is high in persons living with HIV, HAND provides a unique opportunity to study ferroptosis-induced neurodegeneration. Both HIV and combinatory antiretroviral drugs increase the risk of ferroptosis by augmenting ferritin autophagy at the lysosomal level. As many viruses and their proteins exit host cells through lysosomal exocytosis, ferroptosis-driving molecules, iron, cathepsin B and calcium may be released from these organelles. Neurons and glial cells are highly susceptible to ferroptosis and neurodegeneration via white and gray matter damage. Moreover, iron-activated microglia can engage in the aberrant elimination of viable neurons and synapses, further contributing to ferroptosis-induced neurodegeneration. In this mini review, we take a closer look at the role of iron in the pathogenesis of HAND and neurodegenerative disorders. In addition, we describe an epigenetic compensatory system, comprised of bromodomain-containing protein 4 and microRNA-29, that may counteract ferroptosis by activating cystine/glutamate antiporter, while lowering ferritin autophagy and iron regulatory protein-2. We also discuss potential interventions for lysosomal fitness, including ferroptosis blockers, lysosomal acidification, and cathepsin B inhibitors.